CD95-ligand contributes to abdominal aortic aneurysm progression by modulating inflammation. Issue 4 (1st December 2018) - Liu, Zhibo; Fitzgerald, Matthew; Meisinger, Trevor; Batra, Rishi; Suh, Melissa; Greene, Harrison; Penrice, Alexander J; Sun, Lijun; Baxter, B Timothy; Xiong, Wanfen
Abstract: Aims: Abdominal aortic aneurysm (AAA) is one of the number of diseases associated with a prominent inflammatory cell infiltration, matrix protein degradation, and smooth muscle cell apoptosis. CD95 is an inflammatory mediator and an apoptosis inducer. Previous studies have shown elevated expression of CD95 or CD95L in the aortic tissue of AAA patients. However, how the CD95L/CD95 contributes to aneurysm degeneration and whether blocking its signalling would be beneficial to disease progression remains largely unknown. In the present study, we sought to determine the role of CD95L and its downstream target, caspase 8, in AAA progression. Methods and results: By using the CaCl2 murine model of AAA, abdominal aortic aneurysms were induced in C57BL/6 mice. We found that both mRNA and protein levels of CD95L were increased in aneurysm tissue compared with NaCl-treated normal aortic tissue. To determine whether CD95L contributes directly to aneurysm formation, we used CD95L null (CD95L −/− ) mice to examine their response to CaCl2 aneurysm induction. Six weeks after periaortic application of CaCl2, aortic diameters of CD95L −/− mice were significantly smaller compared to CaCl2 -treated wild-type controls. Connective tissue staining of aortic sections from CaCl2 -treated CD95L −/− mice showed minimal damage of medial elastic lamellae which was indistinguishable from the NaCl-treated sham control. Furthermore, CD95L deficiency attenuates macrophage and T cell infiltration into the aortic tissue. To study the role of CD95L in the myelogeous cells in AAA formation, we created chimaeric mice by infusing CD95L −/− bone marrow into sub-leathally irradiated wild-type mice (WT/CD95L −/−BM ). As controls, wild-type bone marrow were infused into sub-leathally irradiated CD95L −/− mice (CD95L −/− /WT BM ). WT/CD95L −/−BM mice were resistant to aneurysm formation compared to their controls. Inflammatory cell infiltration was blocked by the deletion of CD95L on myeloid cells. Western blot analysis showed the levels of caspase 8 in the aortas of CaCl2 -treated wild-type mice were increased compared to NaCl-treated controls. CD95L deletion inhibited caspase 8 expression. Furthermore, a caspase 8-specific inhibitor was able to partially block aneurysm development in CaCl2 -treated aneurysm models. Conclusion: These studies demonstrated that inflammatory cell infiltration during AAA formation is dependent on CD95L from myelogeous cells. Aneurysm inhibition by deletion of CD95L is mediated in part by down-regulation of caspase 8.